1974
DOI: 10.1037/h0036497
|View full text |Cite
|
Sign up to set email alerts
|

Male and female teacher attitudes as a function of students' ascribed motivation and performance levels.

Abstract: Compared the attitudes of 48 male and female undergraduates after they had taught a successful or an unsuccessful simulated student who was labeled as either an overachiever or an underachiever. Data show that (a) the performance of the child was the predominant factor in determining teachers' attitudes; (b) ascriptions modified the performance effect; (c) females differentiated most in their ratings between successful overachievers and unsuccessful overachievers, while males differentiated most in their ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
1

Year Published

1975
1975
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
2
5
1
Order By: Relevance
“…The findings of a study by Brandt and Hayden (1974) lend further support to the findings of Goebes and Shore. In a study to determine the impact of ascribed motivation and performance levels on teacher attitudes, male and female college students were compared after having taught a successful or unsuccessful simulated student who was labeled either an over-or underachiever.…”
Section: Differential Susceptibility To Input Factorssupporting
confidence: 87%
“…The findings of a study by Brandt and Hayden (1974) lend further support to the findings of Goebes and Shore. In a study to determine the impact of ascribed motivation and performance levels on teacher attitudes, male and female college students were compared after having taught a successful or unsuccessful simulated student who was labeled either an over-or underachiever.…”
Section: Differential Susceptibility To Input Factorssupporting
confidence: 87%
“…A few recent studies have used a design which is similar to the one described above but which involved ascriptions about fictitious students. Brandt and Hayden (1974) found that the performance (i.e., success) of a simulated fictitious student was the predominant influence on teacher ratings, although ascriptions of student characteristics made prior to the teaching task significantly affected the teachers' attributions of the quality of student performance itself.…”
mentioning
confidence: 94%
“…Sex was investigated because the; previous work by Brandt and Hayden (1974) had suggested that males performed better in and tended to prefer dealing with failure; situations in comparison with female;s, who tended to perform better in and to prefer success situations. We wante;d to see if this se;x difference!…”
mentioning
confidence: 99%
“…The finding that group assignment (or, which label was assigned to the videotaped student) was a significant predictor of teacher ratings should have been expected, based on the recent findings of other researchers (Brandt § Hayden, 1974;Larsen, 1975) who have demonstrated that giving biased information concei-ning students to the teacher can affect her expectations of and behavior toward the students. The finding also lends support to the proposition that teachers have certain preconceived stereotypical expectancies about the behavior of emotionally disturbed children, and that labelling a child as such calls forth these biases despite behavioral evidence to the contrary (Foster, 1976;Foster, Schmidt, In the present study, the label assigned to the student was a significant predictor of teacher ratings even after all teachers had viewed the child's actual behavior on videotape.…”
Section: Interpretation and Literature Supportmentioning
confidence: 89%
“…Several investigators have demonstrated that giving biased information concerning students to the teacher can affect her expectations of the student, her behavior toward the student and the student's classroom performance (Brandt f, Hayden, 1974;Lars en, 1975 Cahen (1966) demonstrated that teachers of elementary grades display a tendency toward biased test grading when they receive false information concerning students, and that the test grading bias is in the direction of the information bias.…”
Section: Research In Which Expectancy Effect Was Demonstratedmentioning
confidence: 99%